Implementation of Islamic Religious Education in Boarding-Based Public Schools - Febriani, Lara; Junaidi, Junaidi; Belia Sameto, Mayang (Ahlussunnah: Journal of Islamic Education, 2023)
The awareness of Islamic boarding school-based school students in practicing Islamic teachings in their daily lives is the topic of discussion in this research. Based on the problems that the author found in the field, there are still some students who speak impolite words, there are still female students who wear tight clothes and wear hijabs that do not cover their chests, and there are still some students who are not disciplined and behave not in accordance with Islamic teachings as appropriate. students who have undergone Islamic education which has been equipped with strengthening religious knowledge. This research aims to find out how Islamic religious education is implemented in Islamic boarding school-based public schools at Junior high school 4 Lembah Gumanti. This type of research is field research with a qualitative descriptive method. The data collection technique is through interviews, observation, and documentation studies. The author utilized key, main, and supporting informants to obtain data. Then the author carried out data analysis using analytical descriptive analysis. The author uses data triangulation as a technique to check the validity of the data.